Genetic polymorphisms in DNA repair genes and possible links with DNA repair rates, chromosomal aberrations and single-strand breaks in DNA - Vodicka, Pavel; Kumar, Rajiv; Stetina, Rudolf; Sanyal, Somali; Soucek, Pavel; Haufroid, Vincent; Dusinska, Maria; Kuricova, Miroslava; Zamecnikova, Maria; Musak, Ludovit; Buchancova, Jana; Norppa, Hannu; et al. (Carcinogenesis, 2004)
We analysed the associations between genetic polymorphisms in genes coding for DNA repair enzymes XPD (exon 23 A --> C, K751Q), XPG (exon 15 G --> C, D1104H), XPC (exon 15 A --> C, K939Q), XRCC1 (exon 10 G --> A, R399Q) and XRCC3 (exon 7 C --> T, T241 M) and the levels of chromosomal aberrations (CAs) and single-strand breaks (SSBs) in peripheral lymphocytes in a central European population. We also measured the irradiation-specific DNA repair rates and the repair rates of 8-oxoguanines in these individuals. An elevated frequency of CAs was observed in individuals with the XPD exon 23 A allele (AA and AC) genotypes (F = 3.6, P = 0.028, ANOVA). In multifactorial analysis of variance, the XPD exon 23 polymorphism appeared as a major factor influencing CAs (F = 4.2, P = 0.017). SSBs in DNA, on the other hand, were modulated by XPD (F = 4.3, P = 0.023), XPG (F = 4.3, P = 0.024) and XRCC1 genotypes (F = 3.0, P = 0.064). Irradiation-specific DNA repair rates (reflecting mainly base excision repair activity) were affected by XRCC1 (F = 5.9, P = 0.010) and XPC polymorphisms (F = 4.2, P = 0.046, MANOVA). Our results from this study suggest that markers of genotoxicity are associated with polymorphisms in genes encoding DNA repair enzymes.
Keywords: exony; X-ray Repair Cross Complementing Protein 1; poškození DNA; proteiny; Proteins; Codon; Male; Mutagenicity Tests; DNA Damage; Endonucleases; polymorfismus genetický; jednovláknová DNA; Xeroderma Pigmentosum Group D Protein; Exons; chromozomální aberace; Adult; dospělí; jaderné proteiny; mužské pohlaví; DNA vazebné proteiny; Polymorphism, Genetic; DNA Repair; oprava DNA; endonukleasy; Chromosome Aberrations; xeroderma pigmentosum - protein skupiny D; lidé; Transcription Factors; ženské pohlaví; DNA Helicases; transkripční faktory; DNA-helikasy; Humans; protein XRCC1; kodon; DNA, Single-Stranded; Female; Nuclear Proteins; DNA-Binding Proteins; testy genotoxicity